Good Governance in Government Procurement: The Total Cost of Ownership Methodology as a proposal to improve the determination and application of bid evaluation factors - Castro Barriga, Carlos David Alberto (2021)
The rules governing the public procurement cycle grant wide discretion to contracting authorities to determine the award criteria, with price being the sole mandatory award criterion among others of optional character. The application of principles of good governance may contribute to steer the authorities´ discretion by applying instruments and methodologies, such as the so-called Total Cost of Ownership, which allow technically justify the selection of the award criteria with the aim to guarantee an adequate balance between quality and price.